Late gestation predictors of a postnatal biventricular circulation after fetal aortic valvuloplasty. (2nd February 2021) - Beattie, Meaghan J.; Friedman, Kevin G.; Sleeper, Lynn A.; Lu, Minmin; Drogosz, Monika; Callahan, Ryan; Marshall, Audrey C.; Prosnitz, Aaron R.; Lafranchi, Terra; Benson, Carol B.; Wilkins‐Haug, Louise E.; Tworetzky, Wayne
Abstract: Objectives: Fetal aortic valvuloplasty (FAV) for severe aortic stenosis (AS) has shown promise in averting progression to hypoplastic left heart syndrome. After FAV, predicting which fetuses will achieve a biventricular (BiV) circulation after birth remains challenging. Identifying predictors of postnatal circulation on late gestation echocardiography will improve parental counseling. Methods: Liveborn patients who underwent FAV and had late gestation echocardiography available were included (2000–2017, n  = 96). Multivariable logistic regression and classification and regression tree analysis were utilized to identify independent predictors of BiV circulation. Results: Among 96 fetuses, 50 (52.1%) had BiV circulation at the time of neonatal discharge. In multivariable analysis, independent predictors of biventricular circulation included left ventricular (LV) long axis z‐score (OR 3.2, 95% CI 1.8–5.7, p  < 0.001), LV ejection fraction (OR 1.3, 95% CI 1.0–1.8, p  = 0.023), anterograde aortic arch flow (OR 5.0, 95% CI 1.2–20.4, p  = 0.024), and bidirectional or right‐to‐left foramen ovale flow (OR 4.6, 95% CI 1.4–15.8, p  = 0.015). Conclusion: Several anatomic and physiologic parameters in late gestation were found to be independent predictors of BiV circulation after FAV. Identifying these predictors adds to our understanding of LV growth and hemodynamics after FAV and may improve parental counseling. Key Points: What's already known about this topic? Midgestation fetuses with aortic stenosis often progress to hypoplastic left heart syndrome by birth, requiring single ventricle palliation Fetal aortic valvuloplasty has the potential to improve fetal left heart growth and increase the likelihood of achieving postnatal biventricular circulation What does this study add? Our study identifies late gestation predictors of postnatal biventricular circulation after fetal aortic valvuloplasty, including left ventricular long axis dimension z‐score, left ventricular ejection fraction, anterograde aortic arch flow, and bidirectional or right‐to‐left flow across the foramen ovale Determining which patients are likely to achieve biventricular circulation after birth will improve parental counseling and may inform delivery planning